Glutathione peroxidase 1 activity dictates the sensitivity of glioblastoma cells to oxidative stress - Dokić, Ivana; Herold-Mende, Christel (Glia, 2012)
The high intratumoral and intertumoral heterogeneity of glioblastoma (GBM) leads to resistance to different therapies, and hence, selecting an effective therapy is very challenging. We hypothesized that the antioxidant enzyme status is a significant feature of GBM heterogeneity. The most important reactive oxygen/nitrogen species (ROS/RNS) detoxification mechanisms include superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx). Expression and activity of these enzymes and the cellular response to induced oxidative stress were systematically analyzed and compared between GBM cells and nontransformed glial cells of both human and murine origin. Regardless of cell type or species, all tested cells expressed similar amount of catalase and MnSOD. All except one, GBM cell lines exhibited a deficiency in GPx1 expression and activity. Analysis of GBM tissue sections indicated a heterogeneous profile of weak to moderate expression of GPx1 in tumor cells. GPx1 deficiency led to an accumulation of ROS/RNS and subsequent death of GBM cells after induction of oxidative stress. Astrocytes, microglia/macrophages, and glioma stem cell lines expressed active GPx1 and resisted ROS/RNS-mediated cell death. Pharmacological inhibition or siRNA silencing of GPx1 partially reverted this resistance in astrocytes, indicating the contribution of various antioxidant molecules besides GPx1. The GPx1-expressing GBM cell line on the contrary, became extremely sensitive to oxidative stress after GPx1 inhibition. Altogether, these results highlight GPx1 as a crucial element over other antioxidant enzymes for oxidative stress regulation in GBM cells. Mapping the antioxidant enzyme status of GBM may prove to be a useful tool for personalized ROS/RNS inducing therapies. © 2012 Wiley Periodicals, Inc.